Competitive Analysis by Manufactures of Automobiles and Sports Utility Vehicles (SUV), using the Customer Perceived Value as a tool for that purpose (2019)
This article addresses the use of Customer Perceived Value as a tool for Competitive Analysis by manufactures and dealers of Sports Utility Vehicles (SUV). It shows how both, the relative importance of the value attributes and the performance evaluation of the main brands competing in the market, were determined. Then, the way a brand goes about to visualize its competitive position, is illustrated. It also portraits the gap between the ideal value expected by the market and the actual perceived value offer, which is like a “map” of opportunities for existing firms and new comers.